2017 IEEE International Conference on Software Quality, Reliability and Security (QRS) 2017
DOI: 10.1109/qrs.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Towards Ex Vivo Testing of MapReduce Applications

Abstract: Abstract-Big Data programs are those that process large data exceeding the capabilities of traditional technologies. Among newly proposed processing models, MapReduce stands out as it allows the analysis of schema-less data in large distributed environments with frequent infrastructure failures. Functional faults in MapReduce are hard to detect in a testing/preproduction environment due to its distributed characteristics. We propose an automatic test framework implementing a novel testing approach called Ex Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Moran et al [38] have proposed an Ex Vivo testing framework called MapReduce Ex vivo testing (MrExist) that takes advantage of the production information to detect faults. The authors identified some faults in their previous work [39].…”
Section: Ex Vivo Testingmentioning
confidence: 99%
“…Moran et al [38] have proposed an Ex Vivo testing framework called MapReduce Ex vivo testing (MrExist) that takes advantage of the production information to detect faults. The authors identified some faults in their previous work [39].…”
Section: Ex Vivo Testingmentioning
confidence: 99%
“…The concept of ex vivo testing has been already exploited in several contexts. For instance, it has been used to test MapReduce applications based on the data computed in the field, 6 to test autonomous vehicles based on actual usages scenarios, 8 and in self‐adaptive systems 9 . Furthermore field information can be exploited not only to synthesize test cases but also to influence their order of execution 56 or increase the number of tests can be executed across versions 57 .…”
Section: Related Workmentioning
confidence: 99%
“…To timely consider the actual behavior of the services in operation also during in‐house testing stages, it is possible to exploit ex vivo testing strategies 5 . Ex vivo testing uses information extracted from the field to augment existing test cases or produce new test cases that can be used to validate software upgrades consistently with field usages 6,7 . Indeed, ex vivo testing may limit the number of faults that escape in‐house testing due to the lack of knowledge of the behavior of the software in operation, reducing the number of failures that are discovered late in the field, once services have been updated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations